A new way of thinking about environmental building standards: Developing and demonstrating a client-led zero-energy standard. (July 2016) - Parkin, Anna; Mitchell, Andrew; Coley, David
There are over 70 low energy and carbon standards in use around the world. None of these standards have been designed by the clients who pay for and occupy the buildings in question. In this work, the client was asked to define the building code for the construction of a new 2800 m 2 building via a structured survey. The resulting zero-energy standard simply required the building to incur no energy utility bill. One year of monitoring of the completed building was used to see if the standard had been met. The result of this work is a new way of thinking about environmental building standards that solves many of the issues of obtaining and maintaining buy-in from the client. Practical application: This is the first time that the client has played a key role in the definition of a low-energy building standard. Measured energy consumption and renewable energy generation data are presented and demonstrate that the zero-energy criteria were successfully met. This work is important as it shows that the client can have a meaningful input into the design of an environmental standard. The paper should be of interest to architects, engineers, building energy researchers and those interested in methods that can be used to reduce the energy demand of buildings.